Dominant-limb range-of-motion and humeral-retrotorsion adaptation in collegiate baseball and softball position players - Hibberd,E. E.; Oyama, S.; Tatman, J.; Myers, J. B. (Journal of Athletic Training, 2015)
Context: Biomechanically, the motions used by baseball and softball pitchers differ greatly; however, the throwing motions of position players in both sports are strikingly similar. Although the adaptations to the dominant limb from overhead throwing have been well documented in baseball athletes, these adaptations have not been clearly identified in softball players. This information is important in order to develop and implement injury-prevention programs specific to decreasing the risk of upper extremity injury in softball athletes.